Early herding practices revealed through organic residue analysis of pottery from the early Neolithic rock shelter of Mala Triglavca, Slovenia - Lucija Šoberl; Andreja Žibrat Gašparič; Mihael Budja; Richard P. Evershed (Documenta Praehistorica, 2008)
A collection of pottery from the early Neolithic site of Mala Triglavca was analysed with the aim of obtaining insights into vessel use and early animal domestication and husbandry practices in the Adriatic region. Total lipid extracts were submitted to gas chromatography (GC), GC-mass spectrometry (GC-MS) and GC-combustion-isotope ratio MS (GC-C-IRMS) in order to obtain molecular and stable carbon isotope signatures as the basis for determining the nature and origins of the residues. The extracts were dominated by degraded animal fats. The majority (70%) of the total lipid extracts displayed intact triacylglycerol distributions attributable to ruminant adipose and dairy fats, which were subsequently confirmed through C16:0 and C18:0 fatty acid δ13C values.